The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/v14010119
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Molecular Dynamics of SARS-CoV-2 S-Protein in the Presence of Multiple Arbidol Molecules: Interactions and Binding Mode Insights

Abstract: In this work, we evaluated the antiviral activity of Arbidol (Umifenovir) against SARS-CoV-2 using a pseudoviral system with the glycoprotein S of the SARS-CoV-2 virus on its surface. In order to search for binding sites to protein S of the virus, we described alternative binding sites of Arbidol in RBD and in the ACE-2-RBD complex. As a result of our molecular dynamics simulations combined with molecular docking data, we note the following fact: wherever the molecules of Arbidol bind, the interaction of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…This greatly complicates the search for a binding site for entry inhibitors. The possible binding sites were considered: the binding site of Arbidol [ 41 , 42 ] located in the region of heptad repeats (HR1), the region of the likely binding of UA-30 [ 43 ] and nelfinavir [ 44 ], located at the boundary of the two subunits of protein, and the NTD cavity [ 34 ]. Using the Phase plugin [ 45 ] by Schrodinger Suite software, the pharmacophoric profile of binding sites was described.…”
Section: Methodsmentioning
confidence: 99%
“…This greatly complicates the search for a binding site for entry inhibitors. The possible binding sites were considered: the binding site of Arbidol [ 41 , 42 ] located in the region of heptad repeats (HR1), the region of the likely binding of UA-30 [ 43 ] and nelfinavir [ 44 ], located at the boundary of the two subunits of protein, and the NTD cavity [ 34 ]. Using the Phase plugin [ 45 ] by Schrodinger Suite software, the pharmacophoric profile of binding sites was described.…”
Section: Methodsmentioning
confidence: 99%
“…A possible binding site was selected in accordance with early published modelling results shown in [35,36]. Compound 21 can be located in the hydrophobic cleft, located between the α-helices of protomers.…”
Section: Possible Ligand Binding Site Searchmentioning
confidence: 99%
“…Since it is known that pseudoviruses containing the SARS-CoV-2 S protein on their surface either do not infect the original HEK293T cells at all, or infect them with low efficiency [34], we used HEK293T-ACE2 (s) stably exhibiting angiotensin-converting enzyme 2 (ACE2) on its surface, since the SARS-CoV-2 S protein is known to interact with ACE2 as its target [35]. Additionally, HEK293T-hACE2-TMPRSS2 (t) cells obtained transiently and containing both hACE2 and TMPRSS2 on their surface were used, since it was shown that the viral entry requires priming of the S-protein by cellular proteases, such as the TMPRSS2 serine protease, which ensures fusion of viral and cell membranes [36]. According to the results obtained, the best infectivity of pseudoviral particles is observed for HEK293T-hACE2-TMPRSS2 (t) cells, while on HEK293T-ACE2 (s) cells, our SARS-CoV-2 pseudoviruses had a ten-fold lower infectivity and were almost non-contagious in HEK293T cells (Figure 2).…”
Section: Development Of a Pseudovirus Systemmentioning
confidence: 99%
See 2 more Smart Citations